World Economic Outlook, October 2015 : Adjusting to Lower Commodity Prices. (World Economic Outlook; World Economic Outlook ;, 2015)
This issue discusses a number of factors affecting global growth, as well as growth prospects across the world's main countries and regions. It assesses the ongoing recovery from the global financial crisis in advanced and emerging market economies and evaluates risks, both upside and downside, including those associated with commodity prices, currency fluctuations, and financial market volatility. A special feature examines in detail causes and implications of the recent commodity price downturn; analytical chapters look at the effects of commodity windfalls on potential output and of exchange rate movements on trade.